Study of the incorporation of propolis into kombucha bacterial cellulose membrane and its release kinetics - Serpa, Evelin Thayná Barbosa; Rezende, Maira de Lourdes (Disciplinarum Scientia | Naturais e Tecnológicas, 2024)
Kombucha tea is a beverage obtained from a symbiotic culture of acetic acid bacteria (Komagataeibacter, Gluconobacter, and Acetobacter) and lactic acid bacteria (Lactobacillus, Lactococcus), which during the fermentation process, produce bacterial cellulose (BC), a biopolymer free from lignin and hemicellulose. BC is biodegradable, non-toxic, and biocompatible, yet it has been underexplored in the literature. The objective of this study was to establish a methodology for incorporating different concentrations of propolis extract and to evaluate its potential for controlled release through in vitro degradation studies, for therapeutic purposes. Studies have shown that propolis exhibits bactericidal, anti-inflammatory, and tissue regenerative properties, and when applied to biological tissues, it does not cause hypersensitivity reactions. Fourier-transform infrared spectroscopy (FTIR) analyses revealed that kombucha bacterial cellulose membranes incorporating propolis showed good physical interaction. Additionally, ultraviolet-visible spectroscopy (UV-Vis) indicated a reduction in the release rate of propolis into the medium.